Characteristics of rocking vibration based on excitation experiment and numerical analysis of it considering nonlinear effects - Masaaki MIYATA; Katsumi KURITA; Shigeru AOKI (Nihon Kikai Gakkai ronbunshu, 2020)
It is important to understand characteristics of rocking vibration related to overturning small structures inside buildings. In order to understand the overturning of the structure due to rocking vibration by numerical analysis, numerical analysis considering energy loss in a collision and duration of collision is performed by using a quadrilateral hysteresis loop characteristics in which repulsive force is a function of speed. In case that the restitution coefficient is constant and sine wave is used as an input wave, it is good agreement between experiment and numerical analysis response waveforms of rocking vibration in stationary process. However, it is not good agreement in nonstationary process. And it is not good agreement between experiment and numerical analysis response waveforms of rocking vibration using seismic ground motion as an input wave. On the other hand, in case that the restitution coefficient is considering energy loss in a collision and duration of collision, sine wave is used as an input wave, it is good agreement between experiment and numerical analysis response waveforms of rocking vibration in nonstationary process. Also it is good agreement using seismic ground motion as an input wave. From these results, numerical analysis for rocking vibration considering energy loss in a collision and duration of collision is effective using a quadrilateral hysteresis loop characteristics in which repulsive force is a function of speed. And it is effective for this model to understand overturning behavior of small structures in earthquake.